Rethinking Entrepreneurship and School Education: A Developing Country’s Perspective - Dhungana, Nirajan (Economic Journal of Nepal, 2020)
This paper is exploring the role of entrepreneurship literacy education for employment opportunities including self-employment. The concept is explored through the lenses of education as means for economic prosperity, growth and development. The study is carried out by reviewing a range of literature and reviewing the experiences of commercial bank branch managers. These bank managers were inquired utilizing mailed questionnaires about the situation of youth seeking entrepreneurship assistance in their banks and their opinions were sought on how entrepreneurial activities help economic enhancement in the country. The study found that the current education system was neither effective enough for developing entrepreneurship qualities in students nor leading them to entrepreneurship opportunities. It was additionally found that several areas that are appropriate for entrepreneurship are non-incorporated in the current curriculum. The study stresses restructuring the school education by incorporating entrepreneurship competencies, rethinking each course through the perspective of entrepreneurship, adding courses like entrepreneurship guidance within the countries, and arranging extra-curricular activities related to entrepreneurship literacy in collaboration with various stakeholders.